Atypical Ewing sarcoma breakpoint region 1 fluorescence in‐situ hybridization signal patterns in bone and soft tissue tumours: diagnostic experience with 135 cases. Issue 6 (21st September 2016) - Vargas, A Cristina; Selinger, Christina I; Satgunaseelan, Laveniya; Cooper, Wendy A; Gupta, Ruta; Stalley, Paul; Brown, Wendy; Soper, Judy; Schatz, Julie; Boyle, Richard; Thomas, David M; Tattersall, Martin H N; et al.
Abstract : Aims: Recurrent Ewing sarcoma breakpoint region 1 ( EWSR1 ) gene rearrangements characterize a select group of bone and soft tissue tumours. In our routine diagnostic practice with fluorescence in‐situ hybridization (FISH), we have occasionally observed EWSR1 gene rearrangements in tumours not associated classically with EWSR1 translocations. This study aimed to review our institutional experience of this phenomenon and also to highlight the occurrence of unusual EWSR1 FISH signals (i.e. 5′ centromeric region or 3′ telomeric region signals) that do not fulfil the published diagnostic criteria for rearrangements. Methods and results: Using an EWSR1 break‐apart probe, we performed FISH assays on formalin‐fixed paraffin‐embedded tissue sections from 135 bone and soft tissue specimens as part of their routine diagnostic work‐up. EWSR1 gene rearrangements were identified in 51% of cases, 56% of which also showed an abnormal FISH signal pattern (in addition to classically rearranged signals). However, atypical FISH signals were present in 45% of the non‐rearranged cases. In addition, we observed tumours unrelated to those described classically as EWSR1‐ associated that were technically EWSR1 ‐rearranged in 6% of cases. Borderline levels of rearrangement (affecting 10–30% of lesional cells) were present in an additional 17% of these cases. Conclusions: While our study confirmed that FISH is a sensitive and specific tool in the diagnosis of EWSR1 ‐associated tumours, atypical FISH signals and classical rearrangement in entities other than EWSR1‐associated tumours can occur. Therefore, it is essential that the FISH result not be used as an isolated test, but must be evaluated in the context of clinical features, imaging, pathological and immunohistochemical findings.